1991
DOI: 10.1063/1.105915
|View full text |Cite
|
Sign up to set email alerts
|

Critical-current enhancement in particle-irradiated cuprate semiconductors

Abstract: Detailed measurements have been made of the magnetic field (0<H<6 T) and temperature (10 K<T<100 K) dependencies of the critical current density jc in Tl2CaBa2Cu2O8 films before and after irradiation with incremental fluences (0<Φ<3×1016 cm−2) of 2 MeV protons. The results are interpreted quantitatively in terms of radiation-induced changes in (1) the critical temperature, (2) the rate of thermal flux creep, and (3) local scale superconductivity. Radiation-induced enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…reduction in good superconducting material, but this suppression is offset by an increase in the pinning energy.The measurements reported here, when combined with the zero-field observations of Ref 6,. illustrate a delicate interplay between radiation-induced enhancement of the pinning energy and radiation-induced damage of some fraction of the 699 (1) j c-[I3.-TI/Tc(,t) ] 1/2exp, (-at) superconducting material.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…reduction in good superconducting material, but this suppression is offset by an increase in the pinning energy.The measurements reported here, when combined with the zero-field observations of Ref 6,. illustrate a delicate interplay between radiation-induced enhancement of the pinning energy and radiation-induced damage of some fraction of the 699 (1) j c-[I3.-TI/Tc(,t) ] 1/2exp, (-at) superconducting material.…”
mentioning
confidence: 72%
“…6, the combined effect of these two influences is shown to follow the functional dependence where a = 7.5 ± 0.9 x 10-17 cm 2 . We have scaled the pinning force density by the functional dependence of Eq.…”
Section: T (K)mentioning
confidence: 94%
See 1 more Smart Citation
“…Irradiation that generates point defects can enhance J, at low fluences; however, as fluence is increased T, decreases and an increase normal state resistivity results [5, [6]. Considerable less improvement was observed in T1-2212 films for 2 MeV protons [7]. A microstructural study with HRTEM showed damage by 1.…”
Section: Introductionmentioning
confidence: 99%